1999
DOI: 10.1046/j.1365-2036.1999.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Famotidine versus omeprazole in combination with clarithromycin and metronidazole for eradication of Helicobacter pylori—a randomized, controlled trial

Abstract: A 1-week course of clarithromycin and metronidazole in combination with a proton pump inhibitor is SUMMARY Background: One-week low-dose triple therapy is currently considered the gold standard regimen for treatment of Helicobacter pylori infection. However, the mechanisms involved in the synergy between antibiotics and proton pump inhibitors are controversial. Aims: To test the hypothesis that acid suppression represents the crucial mechanism by which the antibacterial activity of antibiotics can be enhanced,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“… ANB, 27–32 0, NTB, 27, 33–45 ANG, 33, 40 38, 41, 46–66 CNG, 22, 31, 53, 54, 57, 60–64, 67–90 ACG, 38, 59, 62, 63, 67, 70, 78, 84, 87, 91–105 MTBG, 34, 38, 39, 58, 99, 106–116 ACMG 82, 117 and CMBR 31, 67, 111, 113, 118 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… ANB, 27–32 0, NTB, 27, 33–45 ANG, 33, 40 38, 41, 46–66 CNG, 22, 31, 53, 54, 57, 60–64, 67–90 ACG, 38, 59, 62, 63, 67, 70, 78, 84, 87, 91–105 MTBG, 34, 38, 39, 58, 99, 106–116 ACMG 82, 117 and CMBR 31, 67, 111, 113, 118 …”
Section: Resultsmentioning
confidence: 99%
“…Clarithromycin, nitroimidazole and a gastric acid inhibitor The most commonly tested regimen in our analysis treated 3128 subjects with clarithromycin, a nitroimidazole and a gastric acid inhibitor (CNG; Table 1). CNG treatment arms came from studies conducted in North America (two studies, 11 arms), South America (one study, two arms), Europe (21 studies, 58 arms), Asia (nine studies, 24 arms) and Australia (one study, four arms) 22, 31, 53, 54, 57, 60–64, 67–90 . The duration of CNG treatment ranged from 5 to 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Some data have been published showing that good H. pylori eradication results can be achieved using H 2 receptor antagonist [9,10,12,28], but there are only a few reports in which proton pump inhibitor and H 2 receptor antagonist were compared in two study arms with the same selection of antibiotics [10–12,28]. A recent randomized, controlled trial showed that famotidine and omeprazole, combined with clarithromycin and metronidazole, were equivalent for cure of H. pylori infection [10]. In contrast, other data showed that ranitidine, when used together with amoxicillin and metronidazole, was less effective than omeprazole [12].…”
Section: Discussionmentioning
confidence: 99%
“…For example, some randomized controlled studies showed the same eradication rates between PPIbased and H2RA-based 1-week triple therapies [65,66]. Meta-analytic studies have shown somewhat lower eradication rates in H2RA-based triple therapies than PPI-based triple therapies [33,67].…”
Section: (1) Ppis and H2ras In Combination Therapiesmentioning
confidence: 97%